2006
DOI: 10.1063/1.2208564
|View full text |Cite|
|
Sign up to set email alerts
|

Raman scattering and high temperature ferromagnetism of Mn-doped ZnO nanoparticles

Abstract: Raman scattering has been used to study the influence of manganese, an effective dopant to obtain ZnO diluted magnetic semiconductors, on the lattice dynamics of ZnO. It is found that Mn doping increases the lattice defects and induces two Raman vibration modes of 275 and 526cm−1. On the other hand, high temperature (TC higher than 350K) ferromagnetism is observed in Zn1−xMnxO (x⩽0.02) nanoparticles. It is found that the ferromagnetism of Zn1−xMnxO nanoparticles is strongly related to defects in ZnO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
115
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(130 citation statements)
references
References 22 publications
9
115
0
1
Order By: Relevance
“…5 shows that the relative intensity of LO and AM mode with respect to the E 2 ͑H͒ intensity increases almost linearly with effective Co concentration. Similar features around 500-600 cm −1 were observed in several works on TM, 18,[23][24][25] Ce, 26 and Sb-doped ZnO samples. 27 In those works the main peak of the broad band is, however, at ϳ530 cm −1 , and it has been attributed to complexes involving intrinsic defects, such as oxygen vacancies ͑V O ͒ and Zn interstitials ͑Zn i ͒.…”
Section: Resultssupporting
confidence: 64%
“…5 shows that the relative intensity of LO and AM mode with respect to the E 2 ͑H͒ intensity increases almost linearly with effective Co concentration. Similar features around 500-600 cm −1 were observed in several works on TM, 18,[23][24][25] Ce, 26 and Sb-doped ZnO samples. 27 In those works the main peak of the broad band is, however, at ϳ530 cm −1 , and it has been attributed to complexes involving intrinsic defects, such as oxygen vacancies ͑V O ͒ and Zn interstitials ͑Zn i ͒.…”
Section: Resultssupporting
confidence: 64%
“…However, when the size of crystal is in nanometre level, first-order Raman scattering is relaxed (for selection rule with k = 0) and phonon scattering is not restricted to the centre of the Brillouin zone 39 . As a result of this, the ZnO nanostructure shows different Raman modes (E 2 high , E 2 low , A 1 (LO), A 1 (TO), E 1 (LO), and E 1 (TO) modes).…”
Section: Figure 2 (Colour Online) (A) Shows the Change In The Averagmentioning
confidence: 99%
“…They explained their data based on the hypothesis that annealing treatments in vacuum increase the number of defects, leading to an enhancement in ferromagnetism whereas annealing in oxygen leads to almost all defects to disappear, concluding the disappearance of ferromagnetism [13]. According to the study made by Wang et al on ZnO:Mn nanoparticles grown by an ultrasonic assisted sol-gel process, ferromagnetic ordering increases with increases in Mn concentrations up to 2 at.%, while for 5 at.%, ferromagnetism is suppressed and a large paramagnetic effect appears [14]. Some studies have also claimed that ferromagnetism in Mn-doped ZnO originates from impurities (manganese oxide or precipitation of secondary phases) or the replacement of Zn 2+ by Mn 2+ in the ZnO host matrix, while other groups have reported that oxygen vacancies cause ferromagnetic ordering in oxide based DMS [15][16][17].…”
Section: Introductionmentioning
confidence: 99%